Pengelompokan provinsi terdampak pandemi covid-19 di Indonesia - Putri, Aufa Qorina; Senjaliana, Fadhiila; Riadi, Rini Aprilianty; Hidayat, Mochtar; Sasmita, Nisa Ummaroh Fajarani; Sari, Alfiani Yulita; Widodo, Edy (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Corona virus is a large group of viruses that cause various types of diseases. Ranging from cough cold to more severe diseases, such as severe acute respiratory syndrome (SARS) and Middle East Respiratory Syndrome (MERS). The new Corona-virus type, 2019 coronavirus novel (2019-nCoV), raises an outbreak known as the Covid-19. The Covid-19 plague makes the whole world frightened. This pandemic makes everyone in the world isolate themselves, keep the distance, and work from home. As a result the world economic sector is disrupted, the tourism sector declines and community activities are hindered. Based on the impacts of the resulting grouping analysis, especially in Indonesia, in the provinces of Indonesia that contracted pandemic Covid-19 using the number of cases of ODP (people in monitoring), PDP (patient in care), positive, died, recovered, and the population projection whose data was taken on 16 June 2020. Using method of analysis K-means Clusteringyang aims to know the general description of the Covid-19 pandemic case in Indonesia, and know how the results grouping the provinces of Indonesia based on the number of Covid-19 pandemic cases. The results of the descriptive analysis were obtained that the highest positive case in DKI Jakarta area was 9,222 cases, and for the lowest case in Aceh region as many as 27 cases. Then for clustering results obtained that obtained 6 clusters, with a level 1 (highest) to Level 6 (at the lowest). In the highest provincial clusters have positive case characteristics, cured, died, ODP, and PDP Supreme, but the projection of the population is low, one of which is Jakarta. While in the lowest provincial clusters have positive case characteristics, cases died, and cases died low, and has a considerable population projection, one of which is Aceh.